Pembelajaran daring materi menyimak cerita pendek pada siswa kelas IV SD menggunakan model pembelajaran inquiry - Herman Pelani; Agni Muftianti (IKIP Siliwangi, 2023)
This study aims to examine the online learning of Indonesian subjects on short story listening material in grade IV elementary school during the COVID-19 pandemic using the Inquiry learning model. Examine teacher and student responses, and examine student difficulties in completing assignments. The research method used is descriptive qualitative. The subjects in this study were 20 fourth grade students of SD Negeri Pasirjambu, totaling 5 male students and 15 female students. The research instruments used were observation sheets, questionnaires or attitude scales, and written tests. The results of this study are that the first scenario and implementation of learning show findings in the field, namely students can learn to listen to short stories better by giving teachers a learning experience using audiovisual media online via whatsapp. Second, the response of teachers and students is very good, Third, the difficulties experienced by students in online learning in listening to short story material using the online inquiry learning model in general, namely the internet network that is less stable, difficult to understand the material and less free to interact with friends, quota limited and limited cellphones, because they have to take turns with other family members. as well as the obstacles experienced by researchers including the lack of stable signal and enough to drain data packets. Based on the results of research and discussion in this study, it can be concluded that online learning on short story listening material in class IV at SDN Pasirjambu is good